Parameterized indoor propagation model for mobile communication links - Zyoud, Al-Hareth; Habaebi, Mohamed Hadi; Islam, Md Rafiqul (John Wiley & Sons, Inc., 2016)
In this letter, a path loss indoor propagation model is parameterized. This model is suitable for application in 4G and wireless networks and maybe applied in both LTE and LTE-A system level simulators. Measurements were conducted at the most popular frequencies for future LTE networks of 1800 and 2600 MHz. In addition, path loss has been examined in terms of various antenna aspects such as polarization and directivity. VC 2016 Wiley Periodicals, Inc. Microwave Opt Technol Lett 58:823–826, 2016; View this article online